Seizure outcome-related factors in autoimmune encephalitis: A systematic review and meta-analysis - Luo, Peijuan; Zhong, Rui; Chen, Qingling; Lin, Weihong (Frontiers in Neurology, 2022)
Abstract Background: Identifying the predictors for seizure outcome in autoimmune encephalitis (AE) and investigating how to prevent persistent seizures would have major clinical benefits effectively. Thus, we aimed to perform a systematic review and meta-analysis to examen seizure outcome-related factors in AE patients. Methods: PubMed and EMBASE were systematically searched from inception to June 10, 2022, for studies investigating seizure outcome-related factors in AE. The pooled effect estimates, including standardized mean differences (SMDs) and odds ratios (ORs) with 95% confidence intervals (CIs), were calculated to estimate the effect of each included factor on the seizure outcome. Results: A total of ten studies were included in the meta-analysis. Our pooled results of this meta-analysis showed that 5 factors were found to increase the risk of persistent seizures in AE patients, including onset with seizures (OR = 2.106, 95% CI = 1.262-3.514, p = 0.004), status epilepticus (OR = 3.017, 95% CI = 1.995-4.563, p ＜ 0.001), EEG abnormalities (OR = 1.581, 95% CI = 1.016-2.46, p = 0.042), MRI abnormalities (OR = 1.554, 95% CI = 1.044-2.283, p = 0.03), and longer time from clinical onset to immunotherapy (SMD = 1.887, 95% CI = 0.598-3.156, p = 0.004). Conclusion: Our meta-analysis indicated that onset with seizures, status epilepticus, EEG abnormalities, MRI abnormalities, and longer time from clinical onset to immunotherapy were risk factors for persistent seizures in AE patients.